Effect of a Single Bout of Resistance Exercise on Arterial Stiffness Following a High-Fat Meal - Augustine, J.; Tarzia, B.; Kasprowicz, A.; Heffernan, K. S. (International Journal of Sports Medicine, 2014)
Consumption of a high-fat meal (HFM) causes postprandial lipemia and vascular dysfunction. Acute resistance exercise (RE) alone may also have a negative effect on vascular function. The purpose of this study was to measure arterial stiffness and postprandial lipemia after a HFM with or without acute RE. 9 recreationally active men (age 24±5 years, BMI 25±3 kg/m2) completed both: (1) HFM alone and (2) HFM+RE in a randomized order. Pulse wave velocity (PWV) from carotid to femoral artery and carotid to radial artery were used as measures of central/aortic and peripheral arterial stiffness, respectively. Circulating triglycerides (TRG) were obtained from finger stick samples as a marker of lipemia. There was a significant condition-by-time interaction for TRG (p<0.05). TRG levels increased significantly following both conditions with a significantly attenuated increase following HFM+RE (p<0.05). There was a significant condition-by-time interaction for peripheral PWV as this parameter increased following HFM, but decreased following HFM+RE (p=0.021). Central PWV did not change with HFM or HFM+RE (p>0.05). Following a HFM, acute RE attenuates postprandial lipemia and improves peripheral arterial stiffness without having a negative effect on central arterial stiffness.
Keywords: vascular function; arterial stiffness; high-fat meal; resistance exercise